Design and fabrication of a microfluidic device for separation of lymphocytes for use as part of a radiation biodosimeter - Yodyiumyuth, Jutima; Sripumkhai, Witsaroot; Ranron, Norabadee; Pattamang, Pattaraluck; Sudprasert, Wanwisa (Engineering and Applied Science Research, 2021)
A radiation biodosimeter is a measure of biological response to radiation that can help determine the exact dose received by using biological markers or radiation-damaged chromosomes using a blood sample as a surrogate tissue. Today, many researchers are interested in micro-technology known as microfluidics which is a device that deals with the theory of fluid flow in sub-millimeter sizes. This research demonstrates the design and fabrication of a microfluidic device for separation of lymphocytes from whole blood using a centrifugal technique. The device is made of a circular PMMA (Sumipex) sheet with a diameter of 90 mm and a thickness of 5 mm, consisting of 12 chambers, each a 3 mm deep hexagonal cavity with a capacity of 120 µL and a straight channel 20 mm long. Efficacy testing was performed by loading 120 µL of whole blood into a chamber and centrifuging at 3000 rpm for 5 min. A yellow layer was removed and overlaid on the Ficoll solution (1.077 g/mL) and centrifuged at the same speed. The peripheral blood mononuclear cells were then removed and stained with trypan blue before counting in the hemocytometer. The results show that the developed microfluidic device is able to separate lymphocytes efficiently, which is used as part of a radiation biodosimeter.